Tourist Activity Experience at Joglo Bu Condro Borobudur: Culinary, Education, and Adventure Tourism - Pranoto; Punjung Rahyuno Dasih (Politeknik Sahid, 2026)
Culinary tourism anchored in traditional architecture is one of the most dynamically growing segments of the global tourism industry, driven by travellers' deepening appetite for genuine cultural encounters. Yet remarkably little scholarship has examined how a single destination can weave culinary experience, cultural education, and adventure tourism into one coherent offer—particularly within the distinctive spatial and symbolic world of Javanese joglo architecture. This study addresses that gap by analysing tourist activity experience at Joglo Bu Condro Resto & Cafe, Borobudur, a destination that integrates traditional Javanese cuisine, cultural education, and adventure tourism within an ensemble of authentic joglo and limasan buildings more than 150 years old. A mixed-methods design was employed: descriptive-exploratory qualitative inquiry as the primary strand, supplemented by a tourist satisfaction survey. Primary data were generated through in-depth interviews with 25 informants, two sessions of Focus Group Discussion, and 30 days of participant observation; satisfaction data were gathered via a Likert-scale questionnaire administered to 120 tourists. Qualitative data were analysed using the interactive model of Miles and Huberman (2014), comprising data reduction, data display, and conclusion drawing. Four dominant themes emerged from the data: (1) traditional culinary authenticity as the principal draw; (2) cultural experience mediated by joglo and limasan architecture; (3) activity diversification through educational and adventure programmes; and (4) integrative management grounded in local wisdom. Theoretically, the findings extend the experience economy framework and the concept of destination authenticity into the understudied context of multi-activity cultural tourism destinations in Indonesia.